Clinical characteristics and potential indicators for definite diagnosis of tuberculous pleural effusion. Issue 1 (4th December 2019) - Yang, Xuemei; Feng, Mingxia; Shen, Ye; Deng, Bo; He, Yong; Cao, Guoqiang
Abstract: Aims: The study aimed to investigate the clinical characteristics of patients with pleural effusion (PE), and explore the effective indicators for definite diagnosis of tuberculous pleural effusion (TBPE). Methods: The adult patients with the presence of PE were enrolled. All the patients received pleural fluid Mycobacterium tuberculosis DNA detection, ADA activity measure and blood T-SPOT.TB test. The clinical characteristics and examination results were recorded. Results: A total of 77 PE patients, including 30 (38.96%) TBPE, 19 (24.67%) malignant PE, 6 (7.79%) empyema, 10 (12.99%) parapneumonic effusion and 12 (15.58%) miscellaneous causes, were enrolled. The diagnostic sensitivity and specificity of pleural fluid M. tuberculosis DNA detection were 33.3% and 100%, respectively. The diagnostic parameters of pleural fluid ADA for TBPE were as follows: sensitivity 50% and specificity 78.7%. In PE cases with pleural fluid lactate dehydrogenase (LDH) more than 500 U/L, the diagnostic values of DNA detection and ADA activity were enhanced, and DNA detection was superior to ADA activity. In addition, the ratio of blood T-STOP.TB A + B to lymphocyte was a potential diagnostic biomarker for TBPE with the sensitivity of 83.3% and the specificity of 66.0%. Conclusion: The clinical significance of pleural fluid M. tuberculosis DNA detection is superior to ADA activity in the diagnosis of TBPE, especially in PE cases with LDH value more than 500 U/L. The ratio of blood T-STOP.TB A + B to lymphocyte is a potential indicator for definite diagnosis of TBPE, with high sensitivity.